A hard nut to crack. Idioms in teaching German as a foreign language - Zenderowska-Korpus, Grażyna (Glottodidactica, 2010)
In the present article I paid attention to teaching idioms in German as a second language. Is the knowledge of idioms possible to master? How many idioms does a student of foreign language need? How should we teach them? How can an idiomatic optimum be achieved? The article starts with a definition of phraseology and idiomatic competence. Then it presents my experience with teaching and knowledge of idioms by students.